Economic Implications of Porcine Cysticercosis Based on Meta- Analysis Estimates of its Prevalence in India - Bhangale, Gajendra N. (International Journal of Bio-resource and Stress Management, 2022)
A meta-analysis of 27 studies systematically obtained from online free databases spanned over period from 2000 to 2019 from different parts of India was done. The pooled estimate of porcine cysticercosis prevalence using random effect model was found 5.21% with 95% CI as 4.04% to 6.52% and 95% PI 1.62% – 15.46%. A wide variation in the prevalence estimates among studies under this analysis was observed which is confirmed through Q statistics =1322.38 (P=0.000). Substantial heterogeneity was observed between studies which is significant (I2=96.52; p=<0.0001 and Tau squared value =0.0341) considering the diversity of populations reported in recruited studies. The sub-group analysis showed significantly higher prevalence in South region followed by North, North-east and West region of India. As regards the methods employed for detection of cysticerci from pigs, it was found that serological method showed higher rate of prevalence. A prevalence of 10.66% (95% CI=5.63% to 15.95%) is reported from those studies which used serological methods whereas carcass examination which is the frequently adopted method detected only 3.71% prevalence (95% CI =2.77% to 4.78%) and other methods such as molecular and histo-pathological studies for prevalence detected cysticercosis in 4.19% (95% CI=2.61% to 5.99%) carcasses over the study period under this meta-analysis. Considering its zoonotic significance as well as economic losses to pork industry, control strategies for PCC need to be devised with regards to health monitoring, hygienic meat practices coupled with education to both the producers and consumers through one health approach.